2018
DOI: 10.1017/s1355617718001054
|View full text |Cite
|
Sign up to set email alerts
|

Action Control Deficits in Patients With Essential Tremor

Abstract: Objective: Essential Tremor (ET) is a movement disorder characterized by action tremor which impacts motor execution. Given the disrupted cerebellar-thalamo-cortical networks in ET, we hypothesized that ET could interfere with the control mechanisms involved in regulating motor performance. The ability to inhibit or stop actions is critical for navigating many daily life situations like driving or social interactions. The current study investigated the speed of action initiation and two forms of action control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Go accuracy was the only behavioral metric which significantly differed between the STN and VIM DBS groups (T(19) = 5.22, p < .0001, d = 2.27), with VIM patients responding more accurately on go-trials. On average, the VIM implant group also responded faster during correct go and failed stop trials and cancelled movements more quickly than STN DBS patients, as indicated by SSRT (which was in the typical elongated range for movement disorder patients: Gauggel et al, 2004;Obeso et al, 2011;Hughes et al, 2019). However, none of these results were significant, indicating comparable task performance between both groups.…”
Section: Behaviormentioning
confidence: 88%
“…Go accuracy was the only behavioral metric which significantly differed between the STN and VIM DBS groups (T(19) = 5.22, p < .0001, d = 2.27), with VIM patients responding more accurately on go-trials. On average, the VIM implant group also responded faster during correct go and failed stop trials and cancelled movements more quickly than STN DBS patients, as indicated by SSRT (which was in the typical elongated range for movement disorder patients: Gauggel et al, 2004;Obeso et al, 2011;Hughes et al, 2019). However, none of these results were significant, indicating comparable task performance between both groups.…”
Section: Behaviormentioning
confidence: 88%
“…Go accuracy was the only behavioral metric which significantly differed between the STN and thalamic groups, with thalamic patients responding more accurately on go-trials (94% vs 83% accuracy, T(19) = 5.22, p < .0001, d = 2.27). Numerically, the thalamic implant group also responded faster during correct go and failed stop trials and cancelled movements more quickly than STN DBS patients, as indicated by SSRT (which was in the typical elongated range for movement disorder patients: Gauggel et al, 2004;Obeso et al, 2011;Hughes et al, 2019). However, none of these results 8 were significant, indicating comparable task performance between both groups.…”
Section: Behaviormentioning
confidence: 89%
“…These results add to a growing body of evidence that ET has an effect on action control beyond tremor. Previous investigations on inhibitory stopping control in ET patients have found slowed action initiation and a reduced ability to stop actions intentionally (Brunamonti et al 2014;Hughes et al 2019). Experimental studies of other cognitive control measures like the Attentional Network Task have also observed differences in performance in ET populations.…”
Section: Discussionmentioning
confidence: 98%
“…Given the unique motor control deficits in ET, recent studies have focused on how disruption to cerebello-thalamocortical circuitries in ET alter the proficiency of executive cognitive systems involved specifically in the control of actions (action control) (Brunamonti et al 2014;Hughes et al 2019). Using the stop-signal task (SST), a well-established paradigm that allows quantification of the latency to initiate and inhibit reactions, ET patients showed both slower reactions to stimulus events as well as slower stopping when presented with a sudden change in stimulus events.…”
Section: Introductionmentioning
confidence: 99%